2010
DOI: 10.2108/zsj.27.91
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration in the HemichordatePtychodera flava

Abstract: When the body of P. flava is severed, the animal has the ability to regenerate its missing anterior or posterior as appropriate. We have focused on anterior regeneration when the head and branchial regions are severed from the body of the worm. After transection, the body wall contracts and heals closed in 2 to 3 days. By the third day a small blastema is evident at the point of closure. The blastema grows rapidly and begins the process of differentiating into a head with a proboscis and collar. At 5 days the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…The close relationship of hemichordates and chordates suggests that a molecular characterization of regeneration in hemichordates might be very revealing. Enteropneusts have excellent regenerative capacities (Tweedell, 1961;Packard, 1968;Rychel and Swalla, 2008;Humphreys et al, 2010;, and impressive anterior and posterior regeneration has been reported in several ptychoderids (Rao, 1955;Rychel and Swalla, 2008;Humphreys et al, 2010) as well as reproduction by fission (Packard, 1968;.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The close relationship of hemichordates and chordates suggests that a molecular characterization of regeneration in hemichordates might be very revealing. Enteropneusts have excellent regenerative capacities (Tweedell, 1961;Packard, 1968;Rychel and Swalla, 2008;Humphreys et al, 2010;, and impressive anterior and posterior regeneration has been reported in several ptychoderids (Rao, 1955;Rychel and Swalla, 2008;Humphreys et al, 2010) as well as reproduction by fission (Packard, 1968;.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, these worms, like hydras and planarians, have amazing regenerative capabilities and they are able to form a complete animal from random portions cut from the body [54]. While iPS and stem cell research in mammals have made remarkable progress recently, regenerative studies in lower animals, especially planarians, have provided fascinating insights into the molecular gene circuitry involved in regeneration and totipotency [55,56].…”
Section: Regenerationmentioning
confidence: 99%
“…While iPS and stem cell research in mammals have made remarkable progress recently, regenerative studies in lower animals, especially planarians, have provided fascinating insights into the molecular gene circuitry involved in regeneration and totipotency [55,56]. Our group and Swalla's lab have just commenced molecular analyses of regeneration in the hemichordate, P. flava, and this work already shows significant promise [54,57,58]. We are excited that powerful, modern, molecular techniques may allow the use of hemichordates to provide a unique perspective in the search for clues about latent regenerative potential in higher chordates, perhaps including humans (Figure 2).…”
Section: Regenerationmentioning
confidence: 99%
“…First, we studied specimens on day one and two of regeneration by electron microscopy (see above) and performed BrdU-pulse experiments on sections to evaluate the structure of the blastema and the exact position of cells in the S-phase. Secondly, we tested whether regeneration in I. pulchra is one continuous process, as in most organisms, or occurs in separate waves as in some other organisms [26-28]. To this end we performed 1-hour pulse experiments on each day of regeneration and covered the entire time of regeneration with successive 12-hour continuous-labelling experiments using 5-ethynyl-2’-deoxyuridine (EdU) to make sure not to miss any peaks in proliferation.…”
Section: Resultsmentioning
confidence: 99%